CORPORATE REPORTING, CORPORATE GOVERNANCE, AND SUSTAINABLE DEVELOPMENT GOALS DISCLOSURES - Dosinta, Nina Febriana; Kurniasih, Erni Panca; Kartika , Metasari; Leorinita, Gita (Jurnal Aplikasi Akuntansi, 2024)
Sustainability Development Goals (SDGs) began to be implemented in 2016 with 17 achievement targets, including increasing human capability and reducing inequality in sustainable development. Supervision from internal company parties by  Corporate Governance (CG) must be carried out by providing SDG information. This research examines the influence of CG on SDGs disclosure. This research used purposive sampling; 33 mining companies that were listed on the Indonesia Stock Exchange for the 2016-2022 period were obtained. The total data used was 231 corporate reporting as research observation data. This research analyzes using panel data regression. The research results show that CG influences SDG disclosure, but only the variables of the existence of the board of commissioners and corporate social responsibility officers show significance. This research implies that CG can maximize support for SDGs, bringing sustainability to shareholders (principals) as company owners. Thus, CG is an essential part of stakeholders' information needs, especially regarding the SDGs.